Correlación de los niveles de proteína cruda del forraje con relación a condición corporal, nitrógeno uréico en sangre y valores del hemograma, en unidades ganaderas lecheras tradicionales y de transición agroecológica (2020)
At present, one of the biggest problems that affect the economic parameters in dairy herds, are the reproductive efficiency indices, which is affected by several aspects among them, the most important nutritional aspect, which is subject to strict balances in the diet, mainly energy-protein. Body condition records are a tool that for more than 25 years has been evaluated and correlated with reproductive and productive parameters, it is presented as the easiest, most economical and subjective way to quantitatively measure these relationships. The correct handling of this tool depends on the experience and management of the data by the producer, technician or advisor, with which we can adjust management practices to improve herd parameters especially in relation to nutrition and reproduction. This document is to review the state of the art, focusing on the relationship between body condition, determination of blood urea nitrogen levels, milk, correlation of hematocrit BUN, creatinine and condition body in agroecological transition herds vs traditional dairy herds.